Isolation and characterization of a sucrose carrier cDNA from spinach by functional expression in yeast. - Riesmeier, J W (1992)
Active loading of the phloem with sucrose in leaves is an essential part of the process of supplying non-photosynthetic tissues with carbon and energy. The transport is protein mediated and coupled to proton-symport, but so far no sucrose carrier gene has been identified. Using an engineered Saccharomyces cerevisiae strain, a cDNA from spinach encoding a sucrose carrier was identified by functional expression. Yeast strains that allow the phenotypic recognition of a sucrose carrier activity were constructed by expressing a cytoplasmic invertase from yeast, or the potato sucrose synthase gene, in a strain unable to transport or grow on sucrose due to a deletion in the SUC2 gene. A spinach cDNA expression library established from the poly(A)+ RNA from source leaves of spinach and cloned in a yeast expression vector yielded transformed yeast clones which were able to grow on media containing sucrose as the sole carbon source. This ability was strictly linked to the presence of the spinach cDNA clone pS21. Analysis of the sucrose uptake process in yeast strains transformed with this plasmid show a pH-dependent uptake of sucrose with a Km of 1.5 mM, which can be inhibited by maltose, alpha-phenylglucoside, carbonyl cyanide m-chlorophenylhydrazone and p-chloromercuribenzenesulfonic acid. These data are in accordance with measurements using both leaf discs and plasma membrane vesicles from leaves of higher plants. DNA sequence analysis of the pS21 clone reveals the presence of an open reading frame encoding a protein with a molecular mass of 55 kDa. The predicted protein contains several hydrophobic regions which could be assigned to 12 membrane-spanning regions.(ABSTRACT TRUNCATED AT 250 WORDS)